Legionella Pneumophila and Dendrimers-Mediated Antisense Therapy - Roghiyeh Pashaei-Asl; Khodadad Khodadadi; Fatima Pashaei-Asl; Gholamreza Haqshenas; Nasser Ahmadian; Maryam Pashaiasl; Reza Hajihosseini Baghdadabadi (Tabriz University of Medical Sciences, 2017)
Finding novel and effective antibiotics for treatment of Legionella disease is a challenging field. Treatment with antibiotics usually cures Legionella infection; however, if the resultant disease is not timely recognized and treated properly, it leads to poor prognosis and high case fatality rate. Legionella pneumophila DrrA protein (Defects in Rab1 recruitment protein A)/also known as SidM affects host cell vesicular trafficking through modification of the activity of cellular small guanosine triphosphatase )GTPase( Rab (Ras-related in brain) function which facilitates intracellular bacterial replication within a supporter vacuole. Also, Legionella pneumophila LepA and LepB (Legionella effector protein A and B) proteins suppress host-cell Rab1 protein's function resulting in the cell lysis and release of bacteria that subsequently infect neighbour cells. Legionella readily develops resistant to antibiotics and, therefore, new drugs with different modes of action and therapeutic strategic approaches are urgently required among antimicrobial drug therapies;gene therapy is a novel approach for Legionnaires disease treatment. On the contrary to the conventional treatment approaches that target bacterial proteins, new treatment interventions target DNA (Deoxyribonucleic acid), RNA (Ribonucleic acid) species, and different protein families or macromolecular complexes of these components. The above approaches can overcome the problems in therapy of Legionella infections caused by antibiotics resistance pathogens. Targeting Legionella genes involved in manipulating cellular vesicular trafficking using a dendrimer-mediated antisense therapy is a promising approach to inhibit bacterial replication within the target cells.